APPLICATION OF THE PRINCIPLES OF INTERIOR DESIGN SPATIAL PLANNING FOR THE THEATER STAGE WITH THE SCRIPT “PADA SUATU HARI” BY ARIFIN C. NOER - Bastiani, Mega Sheli (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2022)
A stage artist (scenographer) uses his ability to create a background image of a performance according to the needs of the script, director, and play. In carrying out his work he must pay attention to artistic elements and involve various fields of science as well as multidisciplinary arts, including architecture for construction work, and interior design for space processing as well as on stage furniture. This paper attempts to describe the application of interior design spatial principles to the needs of stage artistic layout in theater performances, which are taken and studied through interior design principles according to D.K. Ching ie, Equilibrium; Harmony; Unity and Diversity; Rhythm; Emphasis; Scale and Proportion; Color, Texture and Light.Keyword: spatial planning, interior design, stage artistic layout